2022
DOI: 10.3390/molecules27165352
|View full text |Cite
|
Sign up to set email alerts
|

The First Convergent Synthesis of 23,23-Difluoro-25-hydroxyvitamin D3 and Its 24-Hydroxy Derivatives: Preliminary Assessment of Biological Activities

Abstract: In this paper, we report an efficient synthetic route for the 23,23-difluoro-25-hydroxyvitamin D3 (5) and its 24-hydroxylated analogues (7,8), which are candidates for the CYP24A1 main metabolites of 5. The key fragments, 23,23-difluoro-CD-ring precursors (9–11), were synthesized starting from Inhoffen-Lythgoe diol (12), and introduction of the C23 difluoro unit to α-ketoester (19) was achieved using N,N-diethylaminosulfur trifluoride (DAST). Preliminary biological evaluation revealed that 23,23-F2-25(OH)D3 (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We have developed efficient and comprehensive methods to synthesize side-chain fluorinated vitamin D 3 analogues and tested their biological properties. We reported that the configuration of the fluorine atom(s) at the side-chain C23 and C24 positions significantly affected their metabolic resistance to hCYP24A1 and binding affinity for the human vitamin D receptor (hVDR). , Over the course of our research on side-chain fluorovitamin D 3 analogues, we focused on the C22 position this time because the C22 position is located near the C23 position, one of the main metabolic sites for hCYP24A1. Recently, Slominski and co-workers reported that CYP11A1 hydroxylates at the C22, C20, and C17 positions of vitamin D 3 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have developed efficient and comprehensive methods to synthesize side-chain fluorinated vitamin D 3 analogues and tested their biological properties. We reported that the configuration of the fluorine atom(s) at the side-chain C23 and C24 positions significantly affected their metabolic resistance to hCYP24A1 and binding affinity for the human vitamin D receptor (hVDR). , Over the course of our research on side-chain fluorovitamin D 3 analogues, we focused on the C22 position this time because the C22 position is located near the C23 position, one of the main metabolic sites for hCYP24A1. Recently, Slominski and co-workers reported that CYP11A1 hydroxylates at the C22, C20, and C17 positions of vitamin D 3 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…For the synthesis of side-chain fluorovitamin D 3 analogues, we have applied the convergent synthetic method as shown in Scheme . The advantage of this route is that once the side-chain fluoro-CD-ring fragments are synthesized, they can be led to the comprehensive synthesis of side-chain fluorovitamin D 3 derivatives only by changing the A-ring structure. For example, we synthesized a selective sterol regulatory element-binding protein (SREBP)/SREBP cleavage-activating protein (SCAP) suppressor, KK-052, that has a 24,24-difluoro-CD-ring moiety with the tetrazole ring system as an A-ring part .…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic route of the 24-fluoro-CD-rings (5,6) is illustrated in Scheme 6. We synthesized methyl ester (32) from the Inhoffen-Lythgoe diol (1) in three steps [30], and hydrolysis of 32 afforded the corresponding carboxylic acid (28) [31], which was subsequently converted to N-acyloxazolidinones (26,27) via acid chlorides.…”
Section: Via Electrophilic Fluorinationmentioning
confidence: 99%
“…Regio-and stereo-selective fluorination of the vitamin D 3 side-chain is one of the efficient methods used to modulate biological activities, such as binding affinity to the vitamin D receptor (VDR), transactivation activity through the VDR, and metabolic stability against CYP24A1 [1]. We have reported the regio-and stereo-selective fluorination of the CD-ring side-chain starting from the Inhoffen-Lythgoe diol (1) and constructed C26,27-fluoro-CD-rings (2-4) [2,3], C24-fluoro-CD-rings (5-7) [4,5], C23-fluoro-CD-rings (8-10) [6,7], and C22-fluoro-CD-rings (11)(12)(13) [8] (Figure 1) to create a chemical library of side-chain fluorovitamin D 3 analogues using a convergent method (Scheme 1) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of fluorine to the vitamin D3 side-chain is a powerful tool for the application of vitamin D3 to pharmaceuticals, since it significantly affects binding affinity to vitamin D receptor (VDR) and vitamin D binding protein (DBP), while it also confers resistance to CYP24A1 metabolism. [1][2][3][4][5][6][7] 26,26,26,27,27,27-Hexafluoro-1,25-dihydroxyvitamin D3 (falecalcitriol) is one such side-chain fluorinated analogue of active vitamin D3, 1,25-dihydroxyvitamin D3 [1,25(OH)2D3]. This fluorination was designed to resist CYP24A1 metabolism, and falecalcitriol has been clinically applied to treat secondary hyperparathyroidism (Figure 1).…”
Section: Introductionmentioning
confidence: 99%